Antioxidant potential, GC/MS and headspace GC/MS analysis of essential oils isolated from the roots, stems and aerial parts of Nepeta leucophylla. (March 2021) - Sharma, Ajay; Bhardwaj, Garima; Cannoo, Damanjit Singh
Abstract: In the present study headspace GC/MS and GC/MS analysis of essential oils isolated from the roots, stems and aerial (inflorescence and leaves) parts of Nepeta leucophylla was carried out. The essential oils were isolated using Clevenger apparatus by hydro-distillation method. The isolated essential oils were also screened for its total polyphenolic content (TPC) and antioxidant potential using the ferric reducing antioxidant power (FRAP), total antioxidant capacity (TAC) and 2, 2-diphenyl-1-picrylhydrazyl (DPPH) assays. The headspace GC/MS and GC/MS analysis of different parts and essential oils of N. leucophylla revealed the presence of monoterpene hydrocarbons, sesquiterpene hydrocarbons, oxygenated monoterpene hydrocarbons, oxygenated sesquiterpenes hydrocarbons, oxygenated diterpene hydrocarbons and phenolic diterpene hydrocarbons as major classes of volatile constituents. Caryophyllene, germacrene D, α-phellandrene, α-pinene, abieta-9(11), 8(14), 12-trien-12-ol, α-selinene, viridiflorol, totarol, α-terpinene, δ-cadinene are key volatile secondary metabolites identified in different parts of N. leucophylla and its essential oils using headspace GC/MS and GC/MS analysis. All the essential oils had similar TPC values. Further, the antioxidant potential of essential oil isolated from aerial parts was higher than that of roots and stems essential oil in case of all the assays, but the antioxidant potential of both essential oils is less than that of standard used. Furthermore, the correlation among TPC values and different antioxidant assays was also evaluated. The existing results of volatile phytoconstituents and antioxidant potential of essential oils suggest that the N. leucophylla have promising potential to be used in aroma, food and pharmaceutical industries. Graphical abstract: Image 1 Highlights: Nepeta leucophylla is aromatic in nature and widely used for ethnomedicine in the Himalayan region. In Himalayan region N. leucophylla leaves are used to prepare herbal tea and as a remedy against malarial fever. N. leucophylla have also been well recognized for its antioxidant, antibacterial and antifungal potential. Headspace GC/MS and GC/MS analysis showed the presence of diverse classes of volatile constituents in N. leucophylla . The key volatile phytoconstituents noted are caryophyllene, germacrene D, α-pinene, α-selinene, viridiflorol and totarol .